Secrets in the silt. - Lewis, Helen (New Statesman, 2012)
The article profiles paleontologist Jennifer Clack, curator of the Museum of Zoology at Cambridge University in England. Clack's personal and academic background is outlined. The author explains how her discovery of tetrapod fossils in Greenland led to significant changes how scientists view the evolutionary transition from water-based to land-based species.